Engaging users: the future of academic library web sites - Liu, Shu, author; Association of College & Research Libraries, publisher (Colorado State University. Libraries, 2008)
This article examines current academic library web site practices and recommends a conceptual model for future academic library web site design. The author investigated 111 ARL member library web sites and has summarized current site content, design patterns, and innovative features. The author discusses the Web 2.0 principles as defined by Tim O'Reilly and reviews the current literature on Web 2.0 implications for library web services. The author proposes making the academic library web site a virtual place and recommends a conceptual model to inform future academic library web site design based on the investigation and the discussion. Future academic library web sites might feature: 1) user focus, 2) personalization, 3) user engagement, 4) online communities, and 5) remixability.
Keywords: web sites; ARL; Association of Research Libraries; academic libraries; web site design; Web 2.0